Long Run Returns to Education: Does Schooling Lead to an Extended Old Age? - Hans van Kippersluis; Owen O'Donnell; Eddy van Doorslaer (Tinbergen Institute, 2009)
While there is no doubt that health is strongly correlated with education, whether schooling exerts a causal impact on health is not yet firmly established. We exploit Dutch compulsory schooling laws in a Regression Discontinuity Design applied to linked data from health surveys, tax files and the mortality register to estimate the causal effect of education on mortality. The reform provides a powerful instrument, significantly raising years of schooling, which, in turn, has a large and significant effect on mortality even in old age. An extra year of schooling is estimated to reduce the probability of dying between ages of 81 and 88 by 2-3 percentage points relative to a baseline of 50 percent. High school graduation is estimated to reduce the probability of dying between the ages of 81 and 88 by a remarkable 17-26 percentage points but this does not appear to be due to any sheepskin effects of finishing high school on mortality beyond that predicted lin early by additional years of schooling.
Keywords: D30; D31; I10; I12; 330; Health; Mortality; Education; Causality; Regression Discontinuity; Bildungsertrag; Sterblichkeit; Kausalanalyse; Niederlande